Between Aspirations and Law: Protection Consciousness among Congolese Forced Migrants in Rabat. (19th May 2022) - Wissing, Ruben
Abstract: This article analyses forced migrants' perceptions of "protection", coined here as "protection consciousness". The article is built around the voices and lived experiences of Congolese forced migrants in the Moroccan capital and asks: which aspirations mobilise them?; what does "protection" mean for them?; and do they find it in the law, or elsewhere? Fieldwork data was obtained through observations and 15 interviews with Congolese migrants with self-assessed protection needs in Rabat in 2019. A socio-legal analysis of the data leads to three main findings. First, once they are in Morocco, Congolese forced migrants aspire material subsistence and work rather than "protection", and do so irrespective of the original reason that forced them to leave the DRC. Second, they understand and experience "protection" not as a strictly legal concept, but as physical safety, freedom of movement and spiritual and religious comfort. Third, they feel alienated from State law, conceive it as protection-inhibiting rather than protection-enhancing, and prefer to rely on more informal normative and social orders instead.